2008
DOI: 10.1176/appi.ajp.2007.06122089
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid Managed Care and the Distribution of Societal Costs for Persons With Severe Mental Illness

Abstract: Understanding the distribution of societal costs is essential in evaluating health care financing strategies. For adults with mental illnesses, efforts to manage Medicaid expenditures may result in substituting individual and family resources for Medicaid services. Government must focus on the distribution of societal costs since risk-based financing strategies may redistribute costs across the fragmented human services sector and result in unintended system inefficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Otherwise, the program was fee-for-service (although, outpatient Medicaid fees are typically low relative to the market price thereby limiting the supply of services). In 1996 the state implemented in one county (Tampa) a behavioral health carve-out, the impact of which has previously been studied 8-10. The carve-out was capitated and financially at risk for inpatient and outpatient utilization, but not medications.…”
Section: Methodsmentioning
confidence: 99%
“…Otherwise, the program was fee-for-service (although, outpatient Medicaid fees are typically low relative to the market price thereby limiting the supply of services). In 1996 the state implemented in one county (Tampa) a behavioral health carve-out, the impact of which has previously been studied 8-10. The carve-out was capitated and financially at risk for inpatient and outpatient utilization, but not medications.…”
Section: Methodsmentioning
confidence: 99%
“…Because of budget constraints, many states have been transitioning enrollees with disabilities to MMC with a hope of both reducing or stabilizing the state's costs and ensuring better access to health services for enrollees (Sparer, 2012). Yet, previous researchers have reported mixed findings on the impact of MMC (Burns, 2009b;Caswell & Long, 2015;Coughlin et al, 2008;Shern et al, 2007;Yamaki et al, 2019). For persons with early-acquired physical disabilities, Medicaid is a primary source of health services required to meet their complex health care needs, some of which may intensify as they age.…”
Section: Discussionmentioning
confidence: 99%
“…They also found little difference in the costs of physical health services by financial risk arrangement. In a followup study, however, Shern et al 253 found that although the Medicaid managed care plan resulted in cost savings, the savings were either diminished or eliminated when including all societal costs, including private and family expenditures. In particular, people in Medicaid managed care plans appeared to receive significantly more informal caregiving than people in fee-for-service plans.…”
Section: Carve-outs Capitation and Managed Behavioral Healthmentioning
confidence: 99%
“…It is, thus, essential to understand the distributional and societal cost impact of different risk-based financing strategies. 253 Several studies have also highlighted differences in utilization among subpopulations being served in MBHCOs. For example, comparing two captitation models and a fee-for-service model in Colorado's Medicaid program, Kaskie et al 248 found that utilization among older beneficiaries decreased more in the "joint-venture" capitated model, in which a for-profit organization collaborated with a community mental health agency, than in the nonprofit public capitated model.…”
Section: Carve-outs Capitation and Managed Behavioral Healthmentioning
confidence: 99%